"For our dead." The awakening of a power and the mobilization of Ni Una menos [NUM] in Peru in 2016 - Canaza Choque, Franklin Américo (2021)
It interests first of all, return to Peru 2016 to rebuild and be able to explain the social movement of Ni Una Menos (NUM) in a scenario deeply damaged by the increase in violence against women and high rates of femicide. Faced with this, it could be seen that different groups and collectives decided to create an alert on the subject from the networks. The solution suggested that a national mobilization would be called that could account for the critical situation of thousands of women in the country. This claim, finally, detonated on August 13, 2016 in the face of impunity on the part of the Judiciary, when two benign sentences were passed earlier. This is what NUM is about, movement that comes from an inadmissible x-ray and a table accumulated by immense complaints related to acts of violence or femicides presented, where women, for the most part, positioned themselves in the midst of all these problems. In this tense situation, it happens that a wrong institutional decision, could definitely, be the explosive point and the beginning of a flow of claims from the outrage and intervention of the female group or of the groups that gathered NUM.